An Analysis of Second-Year English Department Students' Ability in Using Correlative Conjunctions - Pipin Rahayu; Witri Oktavia (Journal of English Language Teaching, 2020)
This research aimed to know the students’ ability and their problems in using correlative conjunctions. This research is descriptive quantitative research. The population in this research is the second year, fourth semester of 2018 English Department students of Universitas Negeri Padang. The sample of this research is 31 students selected using cluster sampling. The instruments used in this research was grammar test. The test consisted of three parts which 24 questions in total. The data were scored in general and every part of the question to check the quality of the students’ ability in using correlative conjunctions. The data collected and analyzed were categorized.Then, the researcher calculated the mean score of the students to determine the students' ability in using correlative conjunctions for overall and each part.To knowing the students’ problems, the data were analyzed based on the lowest score of the students in answering all the questions. Based on data analysis, it was found that the students’ ability in using correlative conjunctions was fair because the average score of the students was 60,00. The students have very good ability in answering question part 1. It was also found that the students have some difficulties in answering the question in part 3. Furthermore, it was hard for the students to combine sentences using correlative conjunctions.